EFFECTIVE TEACHING METHODS FOR KIDS - Buriyeva Farangiz; Durdona Khamidova (Лучшие интеллектуальные исследования, 2024)
It is known that up to 70% of personal qualities are formed in primary school. And not only basic skills such as reading, writing, solving, listening and speaking are needed by the child in life. Everyone entering this complex and contradictory world needs certain thinking skills and personal qualities. The ability to analyze, compare, highlight the main thing, solve problems, improve oneself and have proper self-esteem, be responsible, independent, create and cooperate - this is a child. must enter this world with